ROLE OF PRE- AND POST-TRANSPLANT FACTORS IN THE DEVELOPMENT OF CORONARY DISEASE OF THE TRANSPLANT HEART - E. K. Kurlianskaya; Yu. P. Ostrovsky; T. A. Trophimova; T. L. Denisevitch; L. V. Ratchok; V. I. Stelmashok; N. V. Semenova (Вестник трансплантологии и искусственных органов)
Aim: to assess the relationship between preand post-transplantation factors and degree of coronary artery lesion, reported by intravascular ultrasound study (IVUS) in patients who underwent orthotopic heart transplantation (OHT) surgery. Materials and methods. The study comprised of 27 patients who underwent OHT more than 2 years before. The age of patients was 46,8 ± 10,4 years old. All of them were preoperatively classified by HLA system. All patients received transthoracic echocardiography at terms of 1, 6, 12 and 24 months after OHT. Coronary angiography (CAG) and IVUS were performed at 24 ± 6 months. Results. In CAG none of the patients showed angiographic signs of CA stenosis, but changes of various degrees were detected by IVUS. Results obtained by IVUS were clustered to select two groups with different degree of coronary artery lesion. The donor’s age in Group 2 was evidently higher compared to Group 1 (34,77 ± 1,03 and 40,00 ± 2,04 years, respectively, p = 0,043). Donor-recipient coincidence frequency was lower in group with significant CA lesion (by 2,36, р = 0,003). The number of cardiac surgeries performed prior to OHT was higher in Group 2 (by 2,8, р = 0,008). Post-transplant factor analysis showed that the number of diabetes mellitus (DM) cases revealed after transplantation was more frequent in Group 2 (by 3,2 vs Group 1, р = 0,021). Conclusion. The degree of CA lesion according to IVUS at 24-month period after OTH was associated with several post-transplant factors, which were the presence of cardiac surgical interventions before transplantation, low HLA donor-recipient coincidence frequency, and donor’s age. The more significant CA lesion is, the more cases of DM after OHT occur.